2015
DOI: 10.1111/andr.12022
|View full text |Cite
|
Sign up to set email alerts
|

‘Carriers of V‐LH among 1593 Baltic men have significantly higher serum LH’

Abstract: SummaryLuteinizing hormone (LH) is a pituitary heterodimeric glycoprotein essential in male and female reproduction. Its functional polymorphic variant (V‐LH) is determined by two missense mutations (rs1800447, A/G, Trp8Arg; rs34349826, A/G, Ile15Thr) in the LH β‐subunit encoding gene (LHB; 19q13.3; 1111 bp; 3 exons). Among women, V‐LH has been associated with higher circulating LH and reduced fertility, but the knowledge of its effect on male reproductive parameters has been inconclusive. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…It was reported that mutations in the LH gene may influence the level of LH serum in men (Punab et al 2015); LH affects Leydig cells, induces testosterone production, and indirectly controls spermatogenesis (McLachlan et al 1996;França et al 2005). Therefore, varying LH levels or function may influence semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that mutations in the LH gene may influence the level of LH serum in men (Punab et al 2015); LH affects Leydig cells, induces testosterone production, and indirectly controls spermatogenesis (McLachlan et al 1996;França et al 2005). Therefore, varying LH levels or function may influence semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…The Trp28Arg and Ile35Thr mutations in exon 2 are the most common LHB allele variant, and the carrier frequency ranges from 0 to 53% in various populations [15], including 11% in Chinese women [16]. The Trp28Arg and Ile35Thr carrier status does not affect T levels and the sperm parameters in adult males, but LH levels increase [17].…”
Section: Discussionmentioning
confidence: 99%
“…Young men (n = 578) were recruited by the AC-TUH between May 2003 and June 2004 in the framework of a prospective study Environment and Reproductive Health (EU sixth FP project QLRT-2001-02911). The study group has been used previously in a number of genetic association studies of male reproductive parameters [ 1 , 9 ]. The current study excluded subjects with severe genital pathologies (cryptorchidism, n = 9) or missing data (no DNA, n = 27; incomplete clinical records, n = 3).…”
Section: Methodsmentioning
confidence: 99%
“…Oligozoospermia was diagnosed according to the World Health Organization criteria valid at the time of recruitment (sperm concentration <20 mln/mL) [ 25 ]. Patients with causal factors for male infertility were excluded from the genetic analysis ( ) [ 2 , 7 , 9 ]. The final number of genotyped patients was 641 (aged 31.6 ± 6.0 years).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation